Literature Review: Chrysomya spp. Flies as Mechanical Vectors of Diarrheal Diseases in Indonesia - Pratiwi, Rezjita Asti (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
The green blowfly (Chrysomya spp.), particularly Chrysomya megacephala, is recognized as a significant mechanical vector in the transmission of diarrheal pathogens. Traditional markets provide an ideal habitat for these flies due to poor sanitation and the presence of organic waste. This study aims to review the role of Chrysomya spp. in spreading diarrheal pathogens in traditional markets. A qualitative descriptive method was applied through literature review of research articles published in the last ten years. The analysis revealed that Chrysomya megacephala carries pathogenic bacteria such as Escherichia coli, Salmonella spp., Shigella spp., Serratia sp., and multidrug-resistant strains like ESBL-producing E. coli. Flies facilitate pathogen transmission via cross-contamination when contacting food after exposure to contaminated materials. These findings highlight the urgent need for vector control and improved market sanitation as key strategies in diarrheal disease prevention.